(untitled) (Human-Computer Interaction Perspectives, 2024)
Interaction design patterns are crucial elements in the design of user interfaces, providing designers with reusable solutions to common design problems. This paper explores the role of interaction design patterns in improving usability and user satisfaction. It discusses the definition of interaction design patterns, their benefits, and their application in various design contexts. The paper also examines best practices for using interaction design patterns effectively, including considerations for accessibility, responsiveness, and user feedback. Case studies are presented to illustrate the successful implementation of interaction design patterns in real-world design projects. Overall, this paper highlights the importance of interaction design patterns as a key tool for creating intuitive and engaging user interfaces.